2020
DOI: 10.1016/j.sjbs.2020.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antifungal activity of Rumex vesicarius L. and Ziziphus spina-christi (L) Desf. Aqueous extracts and assessment of the morphological changes induced to certain myco-phytopathogens

Abstract: Many Plant extracts had proved a potential antifungal activity against a wide range of phytopathogenic fungi. The aim of this study was to evaluate the antifungal activity of the aqueous extracts of Rumex vesicarius L. and Ziziphus spina-christi (L) Desf. against some fungal species. The effect on growth inhibition, conidia germination, sporogenesis, morphological, and ultrastructural characterizations of fungal growth by scanning and transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…The ethanolic extract of A. factorovskyi was prepared, as it has been described before [ 3 ]. Briefly, the fresh plant parts were cut into small pieces, boiled for 15 min, shade dried at an ambient temperature of about 25–30 °C, and then powdered by vigorous grinding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethanolic extract of A. factorovskyi was prepared, as it has been described before [ 3 ]. Briefly, the fresh plant parts were cut into small pieces, boiled for 15 min, shade dried at an ambient temperature of about 25–30 °C, and then powdered by vigorous grinding.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown the antimicrobial activities of some medicinal plants and herbs against different bacterial and fungal species. Of these plants, the members of Asteraceae family, approximately 23,600 species, include different classes of sesquiterpenes that proved many applicable biological activities including the anti-inflammatory, antimicrobial, and anticancer effects, as they are important chemo-preventive agents rich in antioxidants [ 2 , 3 ]. Aaronsohnia factorovskyi (A. factorovskyi ) is a member of Asteraceae family, which includes several medicinal plants, such as Matricaria chamomilla and Helianthus annuus (sunflower) that are characterized by their rich content of sesquiterpenes, flavonoids, and coumarins, which are active constituents of interesting therapeutic importance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies have reported that Z. spina-christi provided a variety of pharmacological activities, including antibacterial, antifungal, antioxidant, antihyperglycemic, and anti-diabetic (Kalayou et al, 2012;Ads et al, 2017;Al-Ghamdi et al, 2017;Alotibi et al, 2020). According to our previous studies, the main phytochemicals were discovered in this plant include alkaloids, flavonoids, and saponins .…”
Section: Introductionmentioning
confidence: 81%
“…The TEM technique by JEM-1011 transmission electron microscope (JEOL Ltd. Inc., Tokyo, Japan) was used to confirm the crystalline structure of the synthesized nanoparticles. The preparation and processing of slides were according to the manufacturer’s instructions, as described previously [ 53 ].…”
Section: Methodsmentioning
confidence: 99%